Investigating associations between appetite-regulating hormones, aggression and craving in males with cannabis use disorder. (1st September 2022) - Kurt Tunagur, Elif Merve; Yazici, Ahmet Bulent; Guzel, Derya; Tunagur, Mustafa Tolga; Ermis, Cagatay; Suda, Mehmet Akif; Yazici, Esra
Abstract: Background: Aggression and craving are common and important withdrawal symptoms in cannabis use disorder. The present study investigated the association between appetite-regulating hormones, aggression, and craving during cannabis withdrawal syndrome (CWS). Methods: Fifty-six male subjects diagnosed with cannabis withdrawal and 45 healthy males were included in the study. The Substance Craving Scale, the Buss–Perry Aggression Questionnaire, and the State-Trait Anxiety Inventory were implemented at baseline. Blood samples were drawn to measure ghrelin, leptin, adiponectin, and resistin levels in the serum. Then, the Point Subtraction Aggression Paradigm (PSAP) was applied. Bloodwork and psychometric assessment procedures were re-implemented after the PSAP. At the 7-day follow-up, psychometric assessments and hormone measurements were repeated in the CWS group. Results: Baseline serum ghrelin and adiponectin levels were lower in the CWS group than controls at baseline. After PSAP, there was a significant increase in ghrelin levels of patients with CWS compared to controls. Patients yielded higher aggression scores, while there was no significant correlation between hormonal changes and PSAP findings. At 7-day follow, ghrelin and resistin levels significantly increased, while serum leptin decreased in patients with CWS. Finally, there was a positive association between craving and resistin levels. Conclusions: Our results present the changes in appetite-regulating hormones. Long-term follow-up studies are needed to shed light on neuroendocrinological aspects of cannabis withdrawal. Highlights: Serum ghrelin and adiponectin levels were lower in subject with cannabis withdrawal, compared to healthy controls. After the aggression-inducing paradigm, there was a significant increase in ghrelin levels in cannabis-users. Serum resistin levels and craving symptoms were positively correlated in subject with cannabis withdrawal.